Adherence to Phosphodiesterase Type 5 Inhibitors in the Treatment of Erectile Dysfunction in Long-Term Users: How Do Men Use the Inhibitors?. Issue 2 (1st June 2014) - Carvalheira, Ana; Forjaz, Vera; Pereira, Nuno Monteiro
Abstract: Introduction: The high effectiveness of phosphodiesterase type 5 inhibitors (PDE5-i) in the treatment of erectile dysfunction (ED) has been demonstrated. However, previous research shows that PDE5-i treatments have high discontinuation rates. Aim: The main goals of this study were to (i) characterize the way men use PDE5-i and (ii) analyze the adherence to treatment, identifying the factors that influence PDE5-i use. Methods: A total of 148 men with clinical diagnosis for ED who maintained the treatment with PDE5-i for over 3 years were interviewed. Interviews concerning their ongoing treatment were carried out using a standardized questionnaire with quantitative and qualitative items. Main Outcome Measures: Physiological measures included the intracavernous alprostadil injection test, associated with penile rigidometry and penile Doppler ultrasound. The qualitative measure included two questions: "Do you use the drug in every sexual intercourse?" and "How do you use the inhibitor?" Results: ED causes were classified as venogenic (31%), arteriogenic (23%), psychogenic (18%), iatrogenic (13%), neurogenic (8%), and diabetic (7%). Participation rate was 71.8%. Of the 148 patients studied, 75% claimed not to use PDE5-i in every intercourse. Most used tadalafil (66%), followed by sildenafil (20%), vardenafil (10%), and 4% alternated the type of medicine. Four main categories emerged concerning the factors that determine the intake of PDE5-i in some intercourse situations and not in others: (i) psychological factors; (ii) medication-related factors; (iii) circumstantial factors; and (iv) relational factors. Conclusion: The analysis of men's narratives revealed a combination of factors that influence the adherence to PDE5-i. The psychological and medication-related factors were the most prevalent. This study highlighted the importance of taking these factors into account, both at the time of prescription and during the follow-up in order to improve adherence.